1995
DOI: 10.1021/bi00020a009
|View full text |Cite
|
Sign up to set email alerts
|

Gene Synthesis, High-Level Expression, and Mutagenesis of Thiobacillus ferrooxidans Rusticyanin: His 85 Is a Ligand to the Blue Copper Center

Abstract: An artificial gene of the blue copper protein rusticyanin from Thiobacillus ferrooxidans was constructed from eight overlapping oligonucleotides in a recursive "one-pot" polymerase chain reaction. The gene was placed behind the T7/lacOR promoter of pET24a and expressed in Escherichia coli as a soluble protein. A purification scheme involving a pH titration step, cation-exchange chromatography, and reverse-phase HPLC separation provided yields of the apoprotein ranging from 70 to 100 mg/L of cell culture; recon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 47 publications
3
52
0
Order By: Relevance
“…Rusticyanin, a blue-copper protein, has been produced in the cytoplasm (Casimiro et al, 1995) or in the periplasm (Bengrine et al, 1998) but, in both cases, the copper was not incorporated and reconstitution in vitro was required. Similarly, copper insertion in subunit II of the aa 3 -type cytochrome oxidase from A. ferrooxidans did not occur when produced in the periplasm of E. coli (J.…”
Section: Discussionmentioning
confidence: 99%
“…Rusticyanin, a blue-copper protein, has been produced in the cytoplasm (Casimiro et al, 1995) or in the periplasm (Bengrine et al, 1998) but, in both cases, the copper was not incorporated and reconstitution in vitro was required. Similarly, copper insertion in subunit II of the aa 3 -type cytochrome oxidase from A. ferrooxidans did not occur when produced in the periplasm of E. coli (J.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the nucleotide and deduced amino acid sequences of the genes for various mononuclear blue copper proteins from different microorganisms became available, notably for azurin, pseudoazurin, amicyanin, and more recently for halocyanin (Canters, 1987;Yamamoto et al, 1987;Arvidsson et al, 1989;Chistoserdov et al, 1991;Ubbink et al, 1991;Mattar et al, 1994). In addition, an artificial gene for rusticyanin has been constructed and amplified using PCR based on the amino acid sequence (Casimiro et al, 1995). The availability of these genes has stimulated research in this area significantly, particularly in the case of plastocyanin and azurin, where various mutant proteins have been engineered.…”
mentioning
confidence: 99%
“…Further, previous reports have indicated that Asp73 might serve as one of the Cu coordinating ligands [56]. In contrast, subsequent site-specific mutants and gene expression results revealed that His85 acts as the Cu coordinating ligand [57]. In our present docking model, we observed that Asp73 is actually situated at the opposite surface of Cu site in RcY and thus is unlikely a coordinate Cu atom.…”
Section: Molecular Interaction Between Cyc2 and Rcy Rcy Is The Intermentioning
confidence: 37%